Epistemology in Latin America - Machuca, Diego Emanuel (2018)
After presenting the current situation of epistemological research in Latin America and part of its history, this entry will address five topics: skepticism (especially in its Pyrrhonian stripe), core epistemology, formal epistemology, Wittgenstein’s thought in connection with epistemology and skepticism, and epistemology of law. It should be noted from the outset that the entry does not purport to provide a comprehensive account of epistemology in Latin America, but rather to paint a general picture of it by focusing on the main issues that have been discussed within that field. We will take into consideration the work of those scholars who have written (in Spanish, Portuguese, or English) on epistemological issues independently of both whether they are currently based in Latin America and whether they have worked in a non-Latin American country for a considerable part of their careers. The touchstone for inclusion was not whether they were born in Latin America—although all but one of those who will be mentioned were born there—but whether they are of Latin American origin, earned a degree from a Latin American university, and worked for at least some time in Latin America, thus receiving (part of) their philosophical education in such a milieu. For this reason, there will be no mention of, e.g., Ernest Sosa’s and Linda Martín Alcoff’s extensive and influential work in epistemology.